(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The most popular man-made construction material in use today is concrete. It is made by combining cementitious ingredients, water, aggregate, and occasionally admixtures, in the proper ratios. Fresh concrete, also referred to as plastic concrete, is newly mixed material that may be moulded into any shape before hardening into the substance known as concrete. A long-lasting chemical interaction between water and cement causes the hardening, which makes concrete stronger over time. The practicality, beauty, and durability of concrete structures built during the first half of the 20th century with plain round mild steel bars and ordinary portland cement (OPC), as well as the ease of obtaining the constituent materials (whatever their qualities), contributed to the widespread use of concrete.